The Effects Of Instruction Using The Arcs Model And Geogebra On Upper Secondary Students' Motivation And Achievement In Learning Combined Transformation - Leong , Koon Wah (Penerbit Universiti Sains Malaysia, 2015)
The purpose of this study was to investigate upper secondary students' motivation and achievement through instruction using the Geogebra by integrating Attention, Relevance, Confidence, and Satisfaction (ARCS) strategies. Specifically, it sought to investigate Form Four students' motivation and achievement of combined transformation before and after the instruction using Geogebra, whether there was any significant difference in students' motivation and achievement after the intervention and what influenced their motivation in learning transformation. An exploratory case study research design was employed. The study sample comprised of 24 Form Four students from a secondary school in Selangor. Course Interest Survey (CIS) and Transformation Geometry Test (TGT) were employed to access students' motivation and achievement before and after the intervention; semi-structured interview was employed to probe the influences on the students' motivation after intervention. Both the paired-samples t-test and Wilcoxon test indicated significant differences in students' achievement (t = –10.025, df = 23, p < .05) and motivation (Z = –4.287, p < .05) after the intervention. Also, this result was further enhanced by the analysis of interview transcripts, which suggested that "learning experience", "learning enhancement" and "interactive learning" were the themes inferred from the participants' interviews.